Autism and mood disorders. (3rd April 2021) - Oakley, Bethany; Loth, Eva; Murphy, Declan G.
Abstract: Individuals with autism experience substantially higher rates of mood problems compared to the general population, which contribute to reduced quality of life and increased mortality through suicide. Here, we reviewed evidence for the clinical presentation, aetiology and therapeutic approaches for mood problems in autism. We identified a lack of validated tools for accurately identifying mood problems in individuals with autism, who may present with 'atypical' features (e.g. severe irritability). Risk factors for mood problems in autism appear to be largely overlapping with those identified in the general population, including shared genetic, environmental, cognitive, physiological/neurobiological mechanisms. However, these mechanisms are exacerbated directly/indirectly by lived experiences of autism, including increased vulnerability for chronic stress - often related to social-communication difficulties(/bullying) and sensory sensitivities. Lastly, current therapeutic approaches are based on recommendations for primary mood disorders, with little reference to the neurobiological/cognitive differences associated with autism. Thus, we recommend: 1) the development and validation of (objective) tools to identify mood problems in autism and measure therapeutic efficacy; 2) an interactive approach to investigating aetiologies in large-scale longitudinal studies, integrating different levels of analysis (e.g. cognitive, neurobiological) and lived experience; 3) testing potential treatments through high-quality (e.g. sufficiently powered, blinded) clinical trials, specifically for individuals with autism.